KERJASAMA INDONESIA-PERANCIS DALAM MEMAJUKAN INDUSTRI FILM NASIONAL (STUDI KASUS : BEKRAF-CNC) - Rudon Vesco Benli Gold; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to examine the form of Indonesia-France cooperation in advancing the national film industry through Bekraf-CnC memorandum of understanding (MoU) that has been signed by the two countries. In the agreed MoU, they agreed to cooperate each other in the fields of production, distribution and exhibition so they can advance the national film industry. This research method use a qualitative research and data collection techniques in the form of document studies or secondary data that author get through the books, journals, and websites which has been reviewed by the author and then summarized into this research, so it will be easier for readers to understand.Indonesian film industry needs to be developed in order to be more advanced, therefore Bekraf and CnC held a cooperation program in the fields of production, distribution and exhibition to support the film industry.Keywords : Bekraf, CNC, MoU, Production, Distribution, Exhibiton